Learning Simulation Xpress and Flow Xpress in SolidWorks : fluid and stress analysis for your 3D design - Perez, Matt (Infinite Skills, 2015)
"In this Learning Simulation Xpress and Flow Xpress in SolidWorks training course, expert author Matt Perez will teach you how to set up and run Simulation Xpress and Flow Xpress studies. This course is designed for users who are already familiar with SolidWorks."--Resource description page.